Multiply: (y3 + 2y2 -5y + 1)(y + 5)

(y^3 + 2y^2 - 5y + 1)(y + 5) = y^4 + 5y^3 + 2y^3 + 10y^2 - 5y^2 - 25y + y + 5; = y^4 + 7y^3 + 5y^2 - 24y + 5

Question

Asked 9/3/2010 4:35:36 PM

Updated 12/2/2014 2:21:57 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

8

(y^3 + 2y^2 - 5y + 1)(y + 5)

= y^4 + 5y^3 + 2y^3 + 10y^2 - 5y^2 - 25y + y + 5;

= y^4 + 7y^3 + 5y^2 - 24y + 5

= y^4 + 5y^3 + 2y^3 + 10y^2 - 5y^2 - 25y + y + 5;

= y^4 + 7y^3 + 5y^2 - 24y + 5

Added 12/2/2014 2:21:57 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [12/2/2014 2:34:09 AM]

Solve: 4 - 9x = 29 - 4x **Weegy:** I'm sorry, i'm not good in math. (More)

Question

Expert Answered

Updated 2/26/2014 7:58:11 PM

1 Answer/Comment

4 - 9x = 29 - 4x

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5

-9x + 4x = 29 - 4

-5x = 25

x = 25/-5

x = -5

Added 2/26/2014 7:58:11 PM

This answer has been confirmed as correct and helpful.

Solve for x: 4 - 9x = 29 - 4x **Weegy:** 4 - 9x = 29 - 4x, -9x + 4x = 29 - 4,
-5x = 25,
x = 25/-5,
x = -5 **User:** Solve for x:
13 + 5x = 22 + 8x **Weegy:** 13 + 5x = 22 + 8x,
5x - 8x = 22 - 13,
-3x = 9,
x = 9/-3, x = -3 (More)

Question

Expert Answered

Updated 2/26/2014 8:00:08 PM

0 Answers/Comments

Solve:
12x + 3 = 3x + 6 **Weegy:** Answer:
a=-5x/2 (More)

Question

Updated 7/16/2014 11:43:58 PM

1 Answer/Comment

12x + 3 = 3x + 6

12x - 3x = 6 - 3

9x = 3

x = 3/9 = 1/3

12x - 3x = 6 - 3

9x = 3

x = 3/9 = 1/3

Added 7/16/2014 11:43:58 PM

This answer has been confirmed as correct and helpful.

Solve.
5x + 5 (x - 3) = 15 **Weegy:** x=3 (which would make it 15 + 0 = 15) (More)

Question

Expert Answered

Updated 12/9/2017 5:04:01 AM

1 Answer/Comment

37,008,748

questions answered

There are no comments.